EFL SENIOR HIGH SCHOOL STUDENTS’ STRATEGIES FOR REDUCING ANXIETY IN SPEAKING PERFORMANCE - Ridwan, Roni; Dayat; Anita, Finny (Journal of English Language Teaching and Education (JELTE), 2024)
This study investigates in depth the strategies used by senior high school students in an English as a Foreign Language (EFL) context to reduce speaking anxiety. Speaking anxiety is a common problem faced by many students, and this study aims to identify the main causes of such anxiety as well as effective strategies applied by students in the classroom. Through semi-structured interviews with a number of students, this study uncovered several key themes, including fear of communicating, fear of negative evaluation from teachers and peers, and various strategies used to overcome anxiety, such as thorough preparation before speaking, relaxation techniques to calm down, and social support from classmates. The findings from this study are expected to provide practical recommendations for educators, so that they can create a more supportive and inclusive learning environment, which in turn can help reduce students' speaking anxiety and increase their confidence in communicating in English. Keywords: Speaking Anxiety, EFL Students, Strategies